Something different - Delidaki, Athena (Health & Research Journal, 2019)
Dear colleagues, My name is Athena Delidaki and I work as the supervisor nurse of “Agioi Anargyroi” Hospital‘s Homecare Nursing Department. I have been involved in homecare nursing since 1993 (22 years till now). My daily program includes scheduled appointments in order to provide nursing care, deliver medication, take blood samples, control and take care of wounds, ulcers, stomia etc. Every Monday detailed weekly schedule is programmed and if necessary emergency appointments are added on. Staff transportation is made by official cars, fully equipped with all the necessary medical materials.